Microbiota changes: the unseen players in cervical cancer progression - Fong Amaris, W. M.; Assumpção, Paulo Pimentel de; Valadares, Leonardo Jacomo; Moreira, Fabiano Cordeiro (Frontiers in Microbiology, 2024)
Cervical cancer ranks among the most prevalent cancers globally with high-risk human papillomaviruses implicated in nearly 99% of cases. However, hidden players such as changes in the microbiota are now being examined as potential markers in the progression of this disease. Researchers suggest that changes in the vaginal microbiota might correlate with cervical cancer. This review provides a comprehensive look at the microbiota changes linked with the advancement of cervical cancer. It also scrutinizes the databases from past studies on the microbiota during healthy and cancerous stages, drawing connections between prior findings concerning the role of the microbiota in the progression of cervical cancer. Preliminary findings identify Fusobacterium spp., Peptostreptococcus spp., Campylobacter spp., and Haemophilus spp., as potential biomarkers for cervical cancer progression. Alloscardovia spp., Eubacterium spp., and Mycoplasma spp. were identified as potential biomarkers for HPV(+), while Methylobacterium spp. may be indicative of HPV(-). However, the study's limitations, including potential biases and methodological constraints, underscore the need for further research to validate these findings and delve deeper into the microbiota's role in HPV development. Despite these limitations, the review provides valuable insights into microbiota trends during cervical cancer progression, offering direction for future research. The review summarizes key findings from previous studies on microbiota during healthy and cancerous stages, as well as other conditions such as CIN, SIL, HPV (+), and HPV (-), indicating a promising area for further investigation. The consistent presence of HPV across all reported cervical abnormalities, along with the identification of distinct bacterial genera between cancerous and control samples, suggests a potential link that merits further exploration. In conclusion, a more profound understanding of the microbial landscape could elucidate the pathogenesis of cervical diseases and inform future strategies for diagnosis, prevention, and treatment.